1994
DOI: 10.4141/cjss94-008
|View full text |Cite
|
Sign up to set email alerts
|

Transport of herbicides and nutrients in surface runoff from corn cropland in southern Ontario

Abstract: . 1994. Transport of herbicides and nutrients in surface runoff from corn cropland in southern Ontario. . the iisk of surface-water contamination by herbicides is greatest following application to cropland when the active ingredients are at the maximum concentration and the soil is the most vulnerable to erosion foilowing cultivaiion. This study determined the magnitude of surface runoff losses of herbicide and^nutrients at, and subsequent to, apptEation. The hrst of tnre'e weekly 10-min,2.'6-rmrainfalls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Since metolachlor was more strongly sorbed on soils than atrazine, it may have a lower mobility in soils (Bowman, 1989;Bowman et al, 1994). This sorption behaviour was in accordance with the Ko» values for the two compounds (metolachlor, 2.9; atrazine, 2.5).…”
Section: Table 1 Best-fit Parameters (K R 1/n) and Goodness Of Fit supporting
confidence: 79%
“…Since metolachlor was more strongly sorbed on soils than atrazine, it may have a lower mobility in soils (Bowman, 1989;Bowman et al, 1994). This sorption behaviour was in accordance with the Ko» values for the two compounds (metolachlor, 2.9; atrazine, 2.5).…”
Section: Table 1 Best-fit Parameters (K R 1/n) and Goodness Of Fit supporting
confidence: 79%
“…The annual average of water runoff from sloped field (5)(6)(7)(8)(9)(10) in Japan had been reported as 2. 8% (1.…”
Section: Surface Flow Watermentioning
confidence: 99%
“…Nitrate is highly soluble and is easily leached to subsurface drains or groundwater. However, a study in Ontario demonstrated that after fertilizer application, significant concentrations of nitrate are found in surface runoff (Bowman et al, 1994). Nitrate loss on the St. Esprit watershed varied seasonally.…”
Section: Seasonal Loss Patternsmentioning
confidence: 99%